2021
DOI: 10.17147/asu-2110-8299
|View full text |Cite
|
Sign up to set email alerts
|

Studie zur Umsetzung und Akzeptanz des SARSCoV- 2-Arbeitsschutzstandards und der SARS-CoV-2- Arbeitsschutzregel für einen erfolgreichen Infektionsschutz im Unternehmen

Abstract: Study of the implementation and acceptance of the SARS-CoV-2 occupational safety and health standard and the SARS-CoV-2 occupational safety and health rules for successful infection control in companies Objectives: This study is intended to provide insights into the real-life implementation of SARS-CoV-2-related occupational safety and health (OSH) measures in German companies. It should also help to identify possible perspectives for further measures to improve the approach of the German accident insurance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…Most employees were instructed by their employer on SARS-CoV-2–related occupational health and safety measures, and more than 70% felt protected by these measures. This is consistent with the information provided by OSH professionals, according to which employees in almost all companies (99%) were informed about prevention and occupational safety measures 16 . Furthermore, a representative survey of employees in Germany found that 79% of employees were satisfied with the protective measures against SARS-CoV-2 infection at work in April 2021 29 .…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Most employees were instructed by their employer on SARS-CoV-2–related occupational health and safety measures, and more than 70% felt protected by these measures. This is consistent with the information provided by OSH professionals, according to which employees in almost all companies (99%) were informed about prevention and occupational safety measures 16 . Furthermore, a representative survey of employees in Germany found that 79% of employees were satisfied with the protective measures against SARS-CoV-2 infection at work in April 2021 29 .…”
Section: Discussionsupporting
confidence: 81%
“…This is again consistent with a survey of OSH professionals, which found that the public sector was less likely than other sectors to have provided a pandemic plan and less likely to inform employees about it. 16 In our study, we observed more severe depressive and anxiety symptoms compared with German normative data from 2006. 30 We retrospectively found substantial (moderate to severe) symptom severity in 16% of participants for spring 2020 and in 29% at the time of the survey, which is consistent with observations in the German general population and similar to a survey of hospital staff at the beginning of the pandemic.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations